(untitled) - Olson, Aaron K. (Hoboken, 2015)
Leading with Strategic Thinking reveals what effective leaders do differently. Eschewing the one-size-fits-all leadership model, this helpful guide outlines four general leadership types and demonstrates how each type achieves success – whether through personal vision, structured process, collaboration, or by empowering others.
Keywords: Lãnh đạo,Giải quyết vấn đề,Leadership,Problem solving